Intraplate Deformation of Oceanic Crust in the West Somali Basin: Insights From Long‐offset Reflection Seismic Data. Issue 2 (17th February 2018) - Sauter, Daniel; Ringenbach, Jean Claude; Cannat, Mathilde; Maurin, Thomas; Manatschal, Gianreto; McDermott, Ken G.
Abstract: Interpretation of new high‐resolution seismic reflection sections reveals intraplate deformation of oceanic crust in the West Somali Basin, between the East Africa margin and the Davie Ridge and its northern extension. The deformation of the oceanic crust takes the form of 1–2 km amplitude buckle folds with a 20–30 km wavelength associated with thrust faults. Reverse faulting is localized along deformation corridors, about 15–30 km wide that we interpret as inherited oceanic fracture zones of the extinct oceanic spreading center. Deformation of the oceanic crust in the westernmost segment started before Hauterivian time ( 132 Ma), while oceanic accretion was ongoing to the east of the Davie Ridge, and stopped at Aptian time ( 120 Ma), when spreading ceased in the whole Somali Basin. Prior to the deformation of the oceanic crust, large volcanic edifices have been emplaced on top of the oceanic crust along preexisting oceanic fracture zones. Well‐defined groups of reflectors, within the mantle (< 20 km below top basement), are interpreted as large shear zones that tapped a connection to deep lithospheric melt channels leading to magmatic intrusions within the crust and emplacement of postseafloor‐spreading volcanic edifices within deformation corridors. Key Points: Buckling and reverse faulting are observed within oceanic crust in the West Somali Basin Deformation of the oceanic crust started before Hauterivian time ( 132 Ma) and stopped at Aptian time ( 120 Ma) Postseafloor‐spreading volcanic edifices have been emplaced on top of the oceanic crust prior to its deformation